Filter Bubbles and Echo Chambers: Pre-digital Origins and Elements of Novelty - Reflections from a Media Education Perspective - Pietro Corazza (Pensa MultiMedia, 2022)
As pointed out by Edgar Morin, a crucial issue for contemporary pedagogy is to understand how to support the new generations in acquiring the ability to orient themselves in the abundance of information made available by digital technologies. In order to do this, a first necessary step is to acquire a greater awareness about the processes through which digital platforms filter the information we have access to. It is therefore relevant to examine how online content personalisation tends to produce filter bubbles and echo chambers, namely to expose users mainly to contents that confirm their preexisting opinions, rather than showing them new stimuli or different worldviews. The origins of such phenomena lie in psychological and social dynamics dating back to long before the appearance of digital technologies: confirmation bias, propensity to homophily and polarisation in homogeneous groups. Nevertheless, the formation of such "bubbles" in the digital contexts shows some novel characteristics that deserve to be considered: every user is alone in his/her bubble, the bubble is invisible and the fact of entering in it does not depend on user's choice. After the analysis of the main features of filter bubbles and echo chambers, I will propose some considerations about how these issues can be dealt with from the perspective of a media education aimed to combine critical analysis and creative practice.